2021
DOI: 10.1021/acsami.0c17773
|View full text |Cite
|
Sign up to set email alerts
|

Direct Surface Passivation of Perovskite Film by 4-Fluorophenethylammonium Iodide toward Stable and Efficient Perovskite Solar Cells

Abstract: Passivating the defective surface of perovskite films is becoming a particularly effective approach to further boost the efficiency and stability of their solar cells. Organic ammonium halide salts are extensively utilized as passivation agents in the form of their corresponding 2D perovskites to construct the 2D/3D perovskite bilayer architecture for superior device performance; however, this bilayer device partly suffers from the postannealing-induced destructiveness to the 3D perovskite bulk and charge tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
83
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(90 citation statements)
references
References 41 publications
7
83
0
Order By: Relevance
“…The ternary‐based devices have a J SC of 26.04 ± 0.23 mA cm −2 , a V OC of 1.08 ± 0.01 V, a FF of 0.82 ± 0.01; the corresponding PCE is 23.06 ± 0.70%, which is among the highest for PSCs with the p–i–n device structure. [ 4,51,52 ] Moreover, the photocurrent hysteresis index (HI) [ 54 ] is 0.035 in the ternary‐based PSCs, down from a HI value of 0.104 in the mixed 2D:3D‐based PSCs. We suggest that this remarkable decrease in photocurrent hysteresis can be attributed to a reduced number of defects (see calculated trap densities in Section S1 of the Supporting Information) and the appearance of chemical interactions between the perovskite and O6T‐4F (specifically, Pb 2+ and C=O).…”
Section: Device Performancementioning
confidence: 99%
“…The ternary‐based devices have a J SC of 26.04 ± 0.23 mA cm −2 , a V OC of 1.08 ± 0.01 V, a FF of 0.82 ± 0.01; the corresponding PCE is 23.06 ± 0.70%, which is among the highest for PSCs with the p–i–n device structure. [ 4,51,52 ] Moreover, the photocurrent hysteresis index (HI) [ 54 ] is 0.035 in the ternary‐based PSCs, down from a HI value of 0.104 in the mixed 2D:3D‐based PSCs. We suggest that this remarkable decrease in photocurrent hysteresis can be attributed to a reduced number of defects (see calculated trap densities in Section S1 of the Supporting Information) and the appearance of chemical interactions between the perovskite and O6T‐4F (specifically, Pb 2+ and C=O).…”
Section: Device Performancementioning
confidence: 99%
“…The rationale is that passivating the harmful defects on the interface and crystal boundaries of perovskite layers may significantly hinder the production of recombination centers and suppress hysteresis. 13,14 There are two passivation methods that reduce perovskite film defects: (a) surface defect passivation and (b) promoting perovskite crystallization, increasing the grain size, and improving the film quality to reduce bulk defects. The reduction of defects in perovskite films improves the PCE and stability of the devices.…”
Section: Introductionmentioning
confidence: 99%
“…First, the original surface grain size will be recrystallized with the participation of 2D perovskite under solution processing conditions, which leads to a change in the grain size. [11,[138][139][140][141][142][143] Zhang and co-workers introduced BAI into the surface of 3D perovskite film by post-treatment process and found that the grain size increases, as shown in Figure 8a. [137] The grain size on the surface increased as the BAI concentration increased.…”
Section: Morphology Modificationmentioning
confidence: 99%